A field test scrutiny on bearing mechanism of super-long bored piles in deep fine silty sand layers. Issue 2 (1st February 2023) - Wang, Xinquan; Que, Yichen; Wang, Kangyu; Diao, Hongguo; Cui, Yunliang; Li, Qing
Abstract: A field test study on bearing mechanism of super-long bored piles in deep fine silty sand layers is performed based on static load testing system of tension-compression anchorage method in actual project. To this end, the load transfer mechanism is scrutinized by analyzing the development and distribution of axial force and shaft resistance of super-long bored piles in deep fine silty sand layers. The results reveal that the load-settlement curve of piles with 20 mm sediment at the bottom demonstrates a steep downward trend, and that of piles with 5 mm sediment at the bottom shows a retard downward trend. Under the action of ultimate load, more than 28% of the settlement on the pile top results from the elastic compression of the pile body. The axial force of piles lessens progressively along the depth direction; however, the decreasing rate varies in different soil layers. Additionally, the shaft resistance in the middle and upper parts of the pile body takes effect before the shaft resistance in lower part of the pile body, which would slightly soften. This study may provide a solid basis for the design, construction, and bearing capacity determination of super-long bored piles in deep silty sand layers.